The sins of the mother : a novel - Steel, Danielle (Delacorte Press, 2012)
Having missed much of her children's lives while she built a home-furnishings empire, Olivia Grayson arranges a family vacation in the Mediterranean in the hopes of rekindling ties only to confront painful interpersonal dynamics and unexpected revelations.